P-P03 Impact of routine nasogastric decompression versus no nasogastric decompression after pancreatoduodenectomy on perioperative outcomes: A meta-analysis of available evidence. (16th December 2021) - Ammar, Khaled; Varghese, Chris; K, Thejasvin; Prabakaran, Viswakumar; Robinson, Stuart; Pathak, Samir; Dasari, Bobby VM; Pandanaboyana, Sanjay
Abstract: Background: This meta-analysis reviewed the current evidence on the impact of routine Nasogastric decompression (NGD) versus no NGD after pancreatoduodenectomy on perioperative outcomes. Methods: PubMed, Medline, Scopus, Embase and Cochrane databases were searched for studies reporting the role of nasogastric tube decompression after pancreatoduodenectomy on perioperative outcomes were retrieved and analysed up to January 2021. Results: Eight studies with total of 1301 patients were enrolled of which 668 patients had routine NGD. Routine NGD was associated with a higher incidence of overall delayed gastric emptying (DGE) and clinically relevant DGE (OR = 2.51, 95% CI; 1.12 - 5.63, I2= 83%, P = 0.03, and OR = 3.64, 95% CI: 1.83 – 7.25, I2 = 54%, P < 0.01, respectively). Routine NGD was also associated with a higher rate of Clavien-Dindo ≥ 2 complications (OR = 3.12, 95% CI: 1.05 – 9.28, I2 = 88%, P = 0.04), and increased length of hospital stay (MD = 2.67, 95% CI: 0.60 – 4.75, I2 = 97%, P = 0.02). There were no significant differences in overall complications (OR = 1.07, 95% CI: 0.79 – 1.46, I2 0%, P = 0.66), or postoperative pancreatic fistula (OR = 1.21, 95% CI: 0.86 – 1.72, I2 = 0%, P = 0.28) between the two groups. Conclusions: Routine NGD may be associated with increased rates of DGE, major complications and longer length of stay after pancreatoduodenectomy.